Rules of the Game and Efficacy of Public Microcredit Schemes: Evidence from Selected Borrowers in Malawi - Richard Zidana; Bryson Nkhoma; Victor Kasulo (Eastern African Journal of Humanities and Social Sciences)
This paper contributes to the scholarly debates that question the efficacy of microcredit schemes in development programming. Dominant political economy debates posit that microcredit schemes have failed to achieve the envisaged financial inclusion and small-scale enterprise development outcomes because the nature of the intervention itself is an imposition by neoliberal promoters on global south economies. It is also argued that local political elites use microcredit programmes as a tool for advancing patronage. Motivated by this foregoing school of thought, we contend in this paper that informal credit management rules that dominate the administration of these schemes, at the expense of clearly spelt-out formal rules made known in the public domain, also contribute to this mission drift. Thus, our aim was to assess how prevailing microcredit-lending rules contribute to non-achievement of development outcomes. Guided by Douglas North’s conceptualisation of rules of the game as our analytical framework, we employed Q methodology to generate key themes that emerged from primary qualitative data collected through in-depth interviews with purposively recruited microcredit clients of the National Economic Empowerment Fund, a public microcredit scheme in Malawi. Findings revealed that microcredit schemes were dominated by informal rules regarding turnaround time, credit appraisal processes, political interference, and misplaced borrower perceptions about the objectives of microcredit schemes. These rules were misaligned to what was promised to potential microcredit borrowers as reflected in the public microcredit’s credit management procedures. We concluded that unless the apparent pervasion of these substitutive informal rules that distort outcomes is curtailed, public microcredit schemes risk becoming an irrelevant strategy for driving small-scale enterprise development agenda in countries like Malawi.